Myoepithlioma of Soft Palate: a case report - Baral, Radha; Ojha, Bidhata; Bajracharya, Dipshikha; Singh, Sumit (Journal of College of Medical Sciences-Nepal, 2018)
Myoepithelioms are rare benign salivary gland tumors representing 1–1.5% of all salivary gland tumors. It was once considered to be one end of the histologic spectrum of pleomorphic adenoma (PA), but myoepitheliomas today are believed to be distinct entity. Herein we report a case of myoepithelioma in a 49 years old female patient with the history of swelling in the soft and hard palate. The diagnosis was made on the basis of histopathological findings and immunohistochemical report.